Evaluation of Surgical Cases of Lung Cancer Admitted in Shiraz Referral Hospitals, Southern Iran in 2009–2022 - Sara Dehghani; Alireza Rezvani; Reza Shahriarirad; Mohammad Sadegh Rajabian; Bizhan Ziaian; Mohammad Javad Fallahi; Parviz Mardani; Armin Amirian (Cancer Reports)
ABSTRACT Introduction Globally, lung cancer is one of the most commonly diagnosed cancers and continues to take the lead in cancer‐related mortality rates. This study aims to provide the latest statistics on the clinical, histopathological, and epidemiological features of lung cancer patients who underwent surgical resection in referral hospitals in Southern Iran. Method In this retrospective study, records of all patients with operable primary and secondary lung cancer who underwent surgical resection of the lung in Shiraz hospitals, located in Southern Iran from November 2009 to May 2022 were screened. Data on demographic, clinical, surgical, and pathological characteristics were analyzed by SPSS software. Results A total of 232 patients with operable lung cancer, including 150 (64.7%) primary cases and 82 (35.3%) secondary cases, underwent 249 operations. The mean age of primary and secondary lung cancer patients was 56.70 ± 13.99 and 45.56 ± 18.88, respectively (p < 0.001). Males accounted for 54.0% and 58.5% of primary and secondary lung cancer patients, respectively. Adenocarcinoma was the most frequent primary pathology, while sarcomas were the most common metastatic lesions. The predominant presenting symptoms were cough (n = 75, 75.0%) and dyspnea (n = 31, 59.7%) in primary and secondary cases, respectively. Involvement of the right lung was more frequent in both groups (65.5% and 53.1% for primary and secondary cases respectively). The most commonly performed surgeries were lobectomy (69.9%) and limited resection (69.8%) for primary and secondary lesions, respectively. Cigarette smoking and extensive resection had a significant association with the in‐hospital mortality rate (p = 0.012 and 0.009 respectively). The overall in‐hospital mortality rate was 3.6% (n = 9). Conclusion Surgical interventions were mostly performed in men and histopathologic subtypes of primary lung adenocarcinoma, metastatic soft tissue sarcoma, and metastatic colon cancer. Smoking and extensive resection accompany a higher risk of short‐term postoperative mortality.